USING SEMANTIC MAPPING IN TEACHING VOCABULARY THROUGH A DESCRIPTIVE TEXT - F42107039, Jenny Emor; Suhartono, Luwandi; Riyanti, Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2012)
Semantic mapping is introduced as a vocabulary presentation technique through descriptive text. The purpose of this research is to know the effectiveness of using semantic mapping in increase the students vocabulary achievement to the seventh grade student of SMPN 1 Samalantan in academic year 2011/2012. The method is through pre-experimental study, using a measurement technique in form of multiple choices and matched words which consists of 20 test items with two supported descriptive text. Based on the data analysis, the mean score of pre-test 4.4, qualifying poor and post-test mean score was 7.4, qualifying average to good. The results confirmed that semantic mapping technique in teaching vocabulary through a descriptive text effectively increase the students achievement of vocabulary. Keywords: Vocabulary, semantic mapping, achievement Abstrak: Semantic mapping adalah teknik yang diperkenalkan sebagai salah satu teknik untuk mempresentasikan kosakata dalam suatu paragraf deskriptiv. Tujuan dari penelitian ini adalah untuk mengetahui semantic mapping efektiv dalam meningkatkan kosakata siswa kelas tujuh di SMPN 1 Samalantan tahun ajaran 2011/2012. Metode yang digunakan adalah metode eksperimen, bentuk penelitian eksperimen adalah multiple choices and matched words dengan jumlah soal 20 item disertai dua paragraf deskriptiv. Berdasarkan data analisis, nilai rata-rata pre-test adalah 4.4, dalam kualifikasi rendah (poor) dan nilai rata-rata post-test adalah 7.4, dalam kualifikasi baik (good). Maka dapat disimpulkan bahwa teknik semantic mapping dalam mengajar kosakata didalam paragraf deskriptiv efektiv menigkatkan kosakata siswa.